A Rare Motor Neuron Deleterious Missense Mutation in the DPYSL3 (CRMP4) Gene is Associated with ALS. Issue 7 (28th May 2013) - Blasco, Hélène; Bernard‐Marissal, Nathalie; Vourc'h, Patrick; Guettard, Yves Olivier; Sunyach, Claire; Augereau, Olivier; Khederchah, Joelle; Mouzat, Kevin; Antar, Catherine; Gordon, Paul H.; Veyrat‐Durebex, Charlotte; Besson, Gérard; et al.
<x xml:space="preserve">Abstract</x> Twenty‐four hours after electroporation, motor neuron survival was decreased to 58 ± 4% (P < 0.001) of expected when expressing mCRMP4 compared with wtCRMP4 or EGFP. Axonal growth, evaluated at 20 hr, was also reduced by 62 ± 10% (P < 0.001) in motor neurons expressing the mutated form of CRMP4 compared with EGFP expressing cells, whereas expression of the wildtype form of CRMP4 did not significantly affect axonal growth (87 ± 7%) <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>